Razsežnost sodobnega ustnega izročila v Reziji (Italija) - Dapit, Roberto (Traditiones (Ljubljana), 2013)
The situation of the oral tradition in Resia Valley (Italy) has been the subject of continual research interest in the decades following the crucial field surveys carried out by Milko Matičetov in the 1960s and 1970s. Recent field research in the same area allows for comparison between contemporary Resian cultural heritage and the state of affairs recorded approximately fifty years ago. Given that oral tradition, especially narratives, seem to be relatively better preserved in Resia than in nearby linguistic areas (e.g. Friulia), the author wishes to ascertain the role of oral tradition in present processes of self representation of the Resian community. Moreover, he depicts the different ways of transmitting and performing oral tradition, recognising its transformations and functions as well as its new dimensions of its symbolic role inside and outside of Resia.
Keywords: ethnology; Etnologija; folk literature; Ljudsko slovstvo; oral literature; folk tradition; Ustno slovstvo; Ljudsko pripovedništvo; folk tales; Slovenci; Slovenes; Resia, Friuli; Rezija; Italija; Italy; ustno izročilo